FEATURES THICKNESS OF SKIN- FAT FOLDS IN PATIENTS WITH ACNE BOYS AND GIRLS FROM PODILLYA TAKING INTO ACCOUNT AND REGARDLESS SOMATOTYPE - Макарчук, І.М. (World of Medicine and Biology, 2015)
Individual properties of the body affect the occurrence of dermatoses, defining the nature of the course and outcome of disease. Actually, somato-biological approach allows more differentially to make diagnosis and tactics necessary therapeutic interventions.Aim of our work – define the features of the thickness of skin and fat folds (TSFF) in patients with acne boys and girls of Podillya with and without regard somatotype.Materials and methodsDone clinical laboratory and anthropological examination of 84 patients with acne boys and 116 girls patients from Podillya. The obtained results are compared with the data of anthropo-somatotypological survey of 150 almost healthy boys and 160 girls of similar age and region of residence from database of Scientific and Research Center Vinnitsa National Medical University named after Pirogov.Used the following methods: general - to verify the diagnosis of acne; anthropometry by the method of V. Bunak in modification of P. Shaparenko; somatotype determination by the method of J. Carter and B. Heath; statistical analysis of obtained results conducted in statistical package license "STATISTICA 6.0" using parametric and nonparametric methods.Results. DiscussionsEstablished that the value of TSFF on the front of the shoulder, on the forearm, under the lower angle of the scapula, on the chest and leg in healthy boys or girls mesomorph and without account of somatotype was significantly (p
Keywords: thickness of skin and fat folds; boys; girls; healthy population; acne